Alternative Chinese Opera in the Age of Globalization Performing Zero - Lei, D. (Studies in International Performance, 2011)
Bringing the study of Chinese theatre into the 21st-century, Lei discusses ways in which traditional art can survive and thrive in the age of modernization and globalization. Building on her previous work, this new book focuses on various forms of Chinese 'opera' in locations around the Pacific Rim, including Hong Kong, Taiwan and California.